2015
DOI: 10.1259/bjr.20150227
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an opposite position aspiration on resolution of pneumothorax following CT-guided lung biopsy

Abstract: respectively. In the other 24 patients (29.3%, 24/82), simple aspiration technique was ineffective. An opposite position (from prone to supine or vice versa) was applied, and a new biopsy puncture site was chosen for reaspiration. This procedure was successful in 22 patients but not in 2 patients who had to have a chest tube insertion. The complete and partial regression rates were 25.0% (6/24) and 66.7% (16/24), respectively. Applying the new method, the total effective rate of aspiration improved significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In cases where aspiration was unsuccessful, the patient was reversed to the side opposite the biopsy puncture site, and aspiration was repeated, which was successful in six out of the remaining seven patients. Zeng et al 44 reported an “opposite position aspiration (from prone to supine or vice versa)” in a larger study sample with an encouraging result. Eighty-two pneumothorax patients were treated with simple manual aspiration that was successful in 58 (70.7%) cases.…”
Section: Management Strategiesmentioning
confidence: 89%
See 1 more Smart Citation
“…In cases where aspiration was unsuccessful, the patient was reversed to the side opposite the biopsy puncture site, and aspiration was repeated, which was successful in six out of the remaining seven patients. Zeng et al 44 reported an “opposite position aspiration (from prone to supine or vice versa)” in a larger study sample with an encouraging result. Eighty-two pneumothorax patients were treated with simple manual aspiration that was successful in 58 (70.7%) cases.…”
Section: Management Strategiesmentioning
confidence: 89%
“…The pathophysiologic basis for this is likely due to many factors. 44 biopsy side down positioning for aspiration may be beneficial for the visceral and parietal pleura symphysis and accumulation of blood within the needle tract, which creates a physical barrier to further leakage of air. This procedure does not increase the alveolar-to-pleural pressure gradient surrounding the leak region compared to aspiration near the initial biopsy site ( Figure 1 ).…”
Section: Management Strategiesmentioning
confidence: 99%
“…The mainly three mechanisms which allow air to enter the pleural space are communication with the outside atmosphere, visceral pleural rupture and the presence of gas-producing organisms (18)(19)(20)(21). And the first two factors A B may contribute to lung biopsy-induced pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…And the first two factors A B may contribute to lung biopsy-induced pneumothorax. An unskilled biopsy may cause direct or indirect communication between the atmosphere and the pleural space, visceral pleural rupture is considered to be the most important contributing factor in lung biopsy-induced pneumothorax especially for pneumothorax in moderate to large in volume (21). The manual aspiration of a pneumothorax was initially reported by Yamagami et al (22) as a method of preventing an increased pneumothorax that would require chest tube placement.…”
Section: Discussionmentioning
confidence: 99%